PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN KEPUTUSAN PEMBELIAN (Studi Pada Kedai Kopi Bertiga Bintaro Tangerang Selatan) - az-zahrah, sarah (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
The purpose of this study is to test the quality of service, promotion, and product quality against purchasing decisions (Three Coffee Studies). The population of this study was visitors to Kopi Bertiga Bintaro, South Tangerang. The research sample used was a minimum of 150 respondents. The data collection method used is a survey, this research instrument is a questionnaire. The data analysis method used is descriptive analysis and hypothesis tested using the Structural Equation Model (SEM) with the Smart-PLS (Partial Least Square) program process. The results of this study show that the variables of Service Quality have a positive and significant effect on Purchasing Decisions, Promotions have a positive and significant effect on Purchasing Decisions, and Product Quality has a positive and significant effect on Purchasing Decisions.